2022
DOI: 10.1002/acn3.51536
|View full text |Cite
|
Sign up to set email alerts
|

The seizure‐inducing plastic explosive RDX inhibits the α1β2γ2 GABAA receptor

Abstract: Objective Royal demolition explosive (RDX) can induce seizures in wildlife and humans following release into the environment or after voluntary consumption. During the Vietnam War, RDX intoxication was the most common cause of generalized seizures in US service personnel, and in some sections of the armed forces, eating of RDX has continued as “a dare” to this day. After its mechanism of action was long unknown, RDX was recently shown to be a GABAA receptor antagonist. We here determined the GABAA receptor sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 24 publications
3
5
0
Order By: Relevance
“…However, we have previously demonstrated that Zolpidem is not effective at mitigating seizures induced by TETS, a GABA A R antagonist that selectively targets α2 and α6 subunits (Mundy et al 2021 ). Our observations that Zolpidem is effective at mitigating RDX-induced seizures supports our previous in vitro and in silico modeling work (Pressly et al 2022 ) that identified the α1 GABA A R subunit as a major target of RDX.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…However, we have previously demonstrated that Zolpidem is not effective at mitigating seizures induced by TETS, a GABA A R antagonist that selectively targets α2 and α6 subunits (Mundy et al 2021 ). Our observations that Zolpidem is effective at mitigating RDX-induced seizures supports our previous in vitro and in silico modeling work (Pressly et al 2022 ) that identified the α1 GABA A R subunit as a major target of RDX.…”
Section: Discussionsupporting
confidence: 91%
“…The significant difference between EC 50 values measured for Zolpidem and 1:1 Zolpidem:compound 2-261, with the EC 50 of the 1:1 combination shifted to the left, suggests that modulation of both subunits is necessary for a more efficient mitigation of seizures. Consistent with the in vitro findings that RDX does not target α6-containing GABA A R (Pressly et al 2022 ), SB-205384 (an α-6 select PAM) was unable to mitigate seizure-like activity. Combined, these data support the hypothesis that the molecular target of RDX is α1β2γ2.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations